A critical analysis and improvement of advanced access content system drive-host authentication. (26th February 2009) - Sui, Jiayuan; Stinson, Douglas R.
This article presents a critical analysis of the Advanced Access Content System drive-host authentication scheme. A few weaknesses are identified which could lead to various attacks on the scheme. In particular, we observe that the scheme is susceptible to unknown key-share and man-in-the-middle attacks. Modifications (based on the ISO and the SIGMA protocols) of the scheme are suggested in order to provide better security. A proof of security of the modified scheme based on the ISO protocol is also presented. The modified schemes achieve better efficiency than the original scheme.